2011
DOI: 10.1136/gutjnl-2011-300367
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus probiotic protects intestinal epithelium from radiation injury in a TLR-2/cyclo-oxygenase-2-dependent manner

Abstract: BackgroundThe small intestinal epithelium is highly sensitive to radiation and is a major site of injury during radiation therapy and environmental overexposure.ObjectiveTo examine probiotic bacteria as potential radioprotective agents in the intestine.Methods8-week-old C57BL/6 wild-type or knockout mice were administered probiotic by gavage for 3 days before 12 Gy whole body radiation. The intestine was evaluated for cell-positional apoptosis (6 h) and crypt survival (84 h).ResultsGavage of 5×107 Lactobacillu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
208
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(217 citation statements)
references
References 46 publications
7
208
1
1
Order By: Relevance
“…LGG or its conditioned medium reduce radiationinduced epithelial injury and improve crypt survival in mice [12]. We preferred to LGG as probiotics because it was shown to be effective especially on the crypts after radiation therapy in experimental studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LGG or its conditioned medium reduce radiationinduced epithelial injury and improve crypt survival in mice [12]. We preferred to LGG as probiotics because it was shown to be effective especially on the crypts after radiation therapy in experimental studies.…”
Section: Discussionmentioning
confidence: 99%
“…Probiotic therapies have been clinically evaluated and used as treatment for clinical conditions, such as human inflammatory bowel diseases, pouchitis, and cancer prevention [12,24]. For inflammatory bowel diseases, recent investigations in mice describe antiapoptotic and anti-inflammatory mechanisms for the probiotic LGG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…113 In summary, while the alterations in gut microbiota between individuals who develop malignancies and those who do not have been well-described, studies exploring the exact pathophysiology of tumorigenesis have been limited. Early, small-scale work has shown that altering the microbiome can decrease the progression to cancer, thus making the microbiota an attractive target in chemoprevention.…”
mentioning
confidence: 99%
“…On the other hand, it is clear that A) it is impossible to sterilize the bowel in the clinical situation; B) antibiotic use tends to select resistant organisms; and C) certain bacteria are more harmful than others. As with IBD, the potential of probiotics in mitigating gastrointestinal inflammation during radiation therapy has generated substantial interest [61][62][63][64] . New techniques for assessment of bacterial flora in the normal state and after exposure to radiation; the development of powerful new gnotobiotic animal models; and improved understanding of the critical importance of the gut microbiome in health and disease are some of the reasons why this promising area of research is constantly evolving.…”
mentioning
confidence: 99%